A murder between the pages - Lillard, Amy (Main Street Book Club, 2020)
"The next in the Main Street Book Club mysteries! It was only a few months ago that the ladies of Arlo's Friday Night Book Club-Fern, Camille, and Helen-solved the murder of the renowned author, Wally Harrison. So when they select Wally's bestseller, Missing Girl, for their next discussion, Arlo is hopeful it will be the end of their mystery hunt. But the women are convinced Missing Girl was inspired by a 50-year-old cold case from their own Sugar Springs, Mississippi-the disappearance of Mary Kennedy-andArlo can do little to stop the book club ladies from investigating. When a young girl is murdered in the exact place the women believe Mary went missing all those years ago, it becomes clear these two cases are connected. And with Arlo's help, they may just be able to crack the case"--